Pengeringan Cabai Merah (Capsicum annuum L.) dengan Kombinasi Oven Microwave dan Kipas Angin - Harum Fadhilatunnur; Subarna Subarna; Zhofran Murtadho; Tjahja Muhandri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
This study was aimed to obtain the best drying method of red chilies (Capsicum annuum L.) using a combination of microwave and fan as well as the characteristics of the dried chilies. Samples were subjected to drying step I, equilibration, and drying step II. Each drying step consisted of heating in microwave followed by blowing with fan repeatedly. The treatment of drying step I were 90 seconds of heating followed by 3 minutes of blowing for 7 cycles and 120 seconds of heating followed by 4 minutes of blowing for 5 cycles. Equlibration was done for 1, 2, and 3 hours. The drying step II consisted of 60 seconds of heating followed by 2 minutes of blowing repeatedly until final moisture content of <10%. All samples were analyzed for their moisture content, color, and vitamin C. The drying rates tend to decrease slowly during drying step I but faster during drying step II. The L* and a* of all samples were not significantly different (p > 0.05). The vitamin C of samples ranged between 66.53-72.68 mg/100 g and significantly decreased with increasing equilibration time. The treatment resulting in the best quality product with shortest drying time was 120 seconds of heating followed by 4 minutes of blowing for 5 cycles, 1 hour of equilibration and 60 seconds of heating followed by 2 minutes of blowing for 10 cycles.